Resistance varying characteristics of DC superconducting fault current limiter in MTDC system. (January 2017) - Zhang, Zhifeng; Guo, Tengxuan; Yang, Jiabin; Qi, Qinquan; Xiao, Liye; Zhang, Guomin; Lin, Liangzhen
Highlights: Considering of operating state of converters, the short-circuit fault in DC side of voltage source converter-based multi-terminal high voltage direct current power transmission (MTDC) is analyzed. With resistive and inductive type fault current limiter, the voltage and current of DC fault circuit is studied and the oscillation features are analyzed theoretically. Simulation model of the MTDC system is built and the results show that the fault currents can be limited effectively by the combination of the SFCL and a reactor. Abstract: Recent years, voltage source converter-based multi-terminal high voltage DC power transmission (MTDC) is widely developed in the world. However, it is difficult for the existing DC breaker to cut off the fault transmission line with large short-circuit fault current. Then, it would be helpful to develop DC fault current limiter for the MTDC system. In this paper, DC superconducting fault current limiter (DCSFCL) is proposed to limit fault current. In order to study the resistance-time performance of the DCSFCL under the rapid change of fault current, a simulation model of Zhoushan MTDC system with DCSFCL is established, and the current-limiting performance of the DCSFCL at different location of the grid is studied. The simulation results show that DCSFCL can effectively limit short-circuit current and improve the operation reliability of MTDC system.